Self-Reduction of Displaced Bucket-Handle Medial Meniscal Tear in a 71-Year-Old Patient: A Case Report. (December 2015) - Ciminero, Matthew L.; Huntley, Samuel R.; Ghasem, Alexander D.; Pitcher, John D.
Background: Bucket-handle meniscal tears are rare in geriatric patients. Displaced bucket-handle meniscal tears are usually treated operatively. Due to the rarity of these tears in elderly patients and conflicting evidence regarding the use of arthroscopy versus conservative treatment, it is valuable to report the clinical presentation, treatment, and outcome of these injuries in elderly patients. Case Description: We describe a 71-year-old man who presented with an acute, displaced, magnetic resonance imaging (MRI)-confirmed right medial meniscal bucket-handle tear with mild effusion and no signs of degenerative joint disease. On physical examination, the patient was unable to fully extend the right leg due to locking of the knee. At 2-month follow-up, MRI showed mild degenerative changes and an anatomically reduced tear. At 6-month follow-up, the patient reported normal, pain-free knee function, and MRI showed the tear healing in anatomic position with minimal inferior surface changes and no effusion. He returned to his pain-free baseline level of physical activity. Literature Review: Upon review of the English literature, this 71-year-old patient is an exceptional case and one of the oldest patients reported to have sustained a displaced medial meniscal bucket-handle tear treated successfully with nonoperative means. Two reported cases of spontaneously reduced meniscal bucket-handle tears were found in the English literature, although both cases were seen in much younger males and involved the lateral meniscus. Clinical Relevance: This case suggests that in elderly patients with displaced medial meniscus bucket-handle tears that reduce spontaneously, the physician can safely and efficaciously use conservative, nonoperative management to achieve restoration of baseline knee function and anatomic meniscal healing while avoiding the risks of arthroscopic surgery. Surgical intervention for reduction without repair may be an available option, but no literature is present to direct care; however, complete documentation as in the current case would be instructive. Katz et al have reported that physical therapy was as efficacious as surgical intervention, although the specific displaced bucket-handle tear was not reported.